Universe is Ether based Single Instruction Quantum Computer his Activity Creates Matter and Life (Global Journal of Science Frontier Research, 2024)
Universe is actually gigant quantum computer (Seth Lloyd) made of ethermulticoloured, multilayered superconductor (Frank Wilczek). Ether constantly creates elementary particles (electron and proton), which are subjet of universe quantum computer macro instruction -Charge Neutralization Process -CNP. After matter creation (periodic table of elements), single cell organisms and life itself (rna and dna) emerged.
Keywords: ether; electron; proton; neutron; cell; rna; dna; neuron